Socioeconomic inequalities in the prevalence, non-awareness, non-treatment, and non-control of diabetes among South Korean adults in 2021. - Seongju Kim; Dong Jun Kim; Hooyeon Lee (PLoS ONE)
The purpose of this study was to investigate socioeconomic inequalities in diabetes prevalence, non-awareness, non-treatment, and non-control among South Korean adults in 2021. This cross-sectional study used data from the 2021 Korean National Health and Nutrition Examination Survey. Relative concentration indices (RCIs) and relative concentration curves stratified by sex and age were used to investigate socioeconomic inequalities in the prevalence, non-awareness, non-treatment, and non-control of diabetes. The prevalence, non-awareness, lack of treatment, and non-control rates in adults aged 30 years and older in 2021 were 15.9%, 29.5%, 33.3%, and 76.1%, respectively. Diabetes was more prevalent in participants under the age of 65 years than those aged 65 years and older for both men (RCI: -0.081, RCI: -0.158, respectively) and women (RCI: -0.203, RCI: -0.292, respectively). The larger the absolute value of the RCI in non-awareness and non-treatment of diabetes in women, the greater the level of socioeconomic inequalities (RCI: 0.182, RCI: 0.154). Socioeconomic inequalities existed in the prevalence of diabetes among both men and women aged under 65 years. In women, socioeconomic inequalities of non-awareness and non-treatment of diabetes were greater than those in men. Thus, preventive care and monitoring are required, particularly among women and individuals under the age of 65 years.